Islamic Caring Mindfulness-based Program for Reducing Fatigue in Indonesian Women with Advanced Breast Cancer - Komariah, Maria; Hatthakit, Urai; Boonyoung, Nongnut (International Journal of Psychosocial Rehabilitation, 2020)
Fatigue is one of the most common symptoms that are still being complained about by cancer patients and those who underwent chemotherapy. This study aims to look at the effects of an Islamic Caring Mindfulness-based (ICMB) program on fatigue among patients afflicted with breast cancer undergoing chemotherapy. 112 women with Stage III breast cancer who are following chemotherapy treatment a the chemotherapy unit in Bandung, Indonesia during the period of February-July 2018, were enrolled in the control and experimental groups in a quasi-experimental study. The researcher assigned participants either to the experimental group (n = 53), receiving both the ICMB program and routine care, or to the control group (n = 59), received only routine care. Data were collected at day 1 (baseline), and day 23. Research tools are the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) and demographic information questionnaires. All statistical analyses were performed through the SPSS software (version 16.0) using the chi-square test and independent t-test. Result: Before the intervention on fatigue, all measures of the two groups were equal (P = 0.117). However, a significant difference was observed between the groups on day 23 (P = 0.001) after the intervention. Conclusion: The findings indicate that a nurse-led ICMB program can be used to reduce fatigue among patients with advanced breast cancer who are undergoing chemotherapy.